2001
DOI: 10.1086/321288
|View full text |Cite
|
Sign up to set email alerts
|

A Schizophrenia-Susceptibility Locus at 6q25, in One of the World's Largest Reported Pedigrees

Abstract: We have completed a genome scan of a 12-generation, 3,400-member pedigree with schizophrenia. Samples from 210 individuals were collected from the pedigree. We performed an "affecteds-only" genome-scan analysis using 43 members of the pedigree. The affected individuals included 29 patients with schizophrenia, 10 with schizoaffective disorders, and 4 with psychosis not otherwise specified. Two sets of white-European allele frequencies were used-one from a Swedish control population (46 unrelated individuals) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 35 publications
2
94
1
2
Order By: Relevance
“…In a sample of large Eastern Canadian SZ families, Brzustowicz et al 13 observed under parametric linkage analysis a lod score of 6.5 in chromosome 1q21-q22 under the assumption of heterogeneity. Lindholm et al 14 reported, in one very large SZ pedigree of Sweden, a lod score of 6.6 in 6q25.2 and described a 6 cM haplotype in this region segregating with the disorder. However, we 15 and others, [16][17][18][19][20][21][22] as well as a meta-analysis, 23 reported negative results in 1q21-q22, whereas two studies 24,25 provided confirmations.…”
mentioning
confidence: 99%
“…In a sample of large Eastern Canadian SZ families, Brzustowicz et al 13 observed under parametric linkage analysis a lod score of 6.5 in chromosome 1q21-q22 under the assumption of heterogeneity. Lindholm et al 14 reported, in one very large SZ pedigree of Sweden, a lod score of 6.6 in 6q25.2 and described a 6 cM haplotype in this region segregating with the disorder. However, we 15 and others, [16][17][18][19][20][21][22] as well as a meta-analysis, 23 reported negative results in 1q21-q22, whereas two studies 24,25 provided confirmations.…”
mentioning
confidence: 99%
“…The finding in 6q25 for SCZ is probably a product of the very significant score that was obtained in the study of one pedigree from Sweden. 30 The 6q23 finding in BPD cannot be attributed to a specific study as none reported significant findings in this exact location. It is noteworthy, however, that significant evidence for linkage in this location was found in Arab pedigrees from Israel 31,32 under a broad diagnostic model that included some patients with affective symptoms (mainly SA disorder, both types).…”
Section: Discussionmentioning
confidence: 86%
“…The first focus (from proximal to distal) of interest on chromosome 6q (F-1) is centered at 96 Mb with significant results for SCZ-related disorders demonstrated by two studies, 25,27 and supported from findings in SCZ, 24,26,28,30 and for both SCZ and BPD. 39 The second focus of findings (F-2) is at 105 Mb, mainly in BPD, with one significant study 42 and several supporting studies, 37,38,46 but also studies on SCZ, 24 autism 52 and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dans un grand échantillon de l'est du Canada, le groupe de Anne Bassett [27] a observé, en analyse de liaison paramétrique, un lod score de 6,5 sur le chromosome 1q21-q22, lié à 75 % des familles de l'échantillon. E. Lindholm et al [28] viennent de rapporter un lod score de 6,6 avec des marqueurs situés sur le chromosome 6q25.2, avec un haplotype de 6 cM ségrégant avec la maladie dans des familles de Suède affectées par la SZ. Ces études suggèrent la possibilité d'effets de gènes majeurs pour chacune des psychoses, mais dans de petits sousensembles de familles, confirmant ainsi l'existence d'une hétérogénéité et d'une transmission complexe de la SZ et de la BP.…”
Section: éCueils Méthodologiques à éViter Dans La Nouvelle Générationunclassified